Corporate Financial Distress Prediction Using the Risk-related Information Content of Annual Reports - Hájek, Petr; Munk, Michal (Elsevier Limited, 2024)
This study presents a financial distress prediction model focusing on the linguistic analysis of risk-related sections of corporate annual reports. Here, we introduce a novel methodology that leverages BERT-based contextualized embedding models for nuanced extraction of financial sentiment and topic coherence. This stands in contrast to existing research, which predominantly relies on dictionary-based or non-contextual word embeddings and addresses their limitations in context sensitivity. Furthermore, we apply an innovative financial distress prediction model that combines the robust XGBoost algorithm with unsupervised outlier detection techniques. This hybrid model is specifically designed to tackle the issue of class imbalance, a persistent challenge in financial distress prediction. The efficacy of the proposed model is empirically validated using a comprehensive dataset of 2545 companies listed on major global stock exchanges. Our findings indicate that the introduced model not only significantly outperforms most existing state-of-the-art financial distress prediction models in terms of predictive accuracy, but also significantly outperforms the Loughran & McDonald dictionary-based approach and the Word2Vec model, underlining its potential as a superior analytical tool for financial distress prediction.
Predikce finanční tísně korporací pomocí informací o rizicích z výročních zpráv
Keywords: Financial distress; Prediction; Annual report; Financial sentiment; Semi-supervised learning; XGBoost; Finanční potíže; Predikce; Výroční zpráva; Finanční sentiment; Semi-supervizované učení; XGBoost